Analisis Partisipasi Anggota Dan Perkembangan Sisa Hasil Usaha (SHU) Dalam Rangka Meningkatkan Pengembangan Koperasi Polres Solok Kota - Yuli Carmela; Ida Nirwana; Arfimasri, Arfimasri (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted at the Solok City Police Cooperative. The purpose of this research is to find out how much Member Participation and the Development of Remaining Business Results make the cooperative more developed. In this study, the population is cooperative members, totaling 30 people. With this type of quantitative research and sampling technique using purposive sampling method. The data collection technique used is by using a questionnaire/questionnaire. Based on multiple linear regression analysis of the variables of Member Participation and the Development of Remaining Business Results affect the Cooperative Development Y = 7,435 + 0,227X1 + 0,612X2 + e. From the t-test that was carried out, it was found that the variable X1 Member Participation had a significant effect on Cooperative Development with tcount 2.517 > ttable 2.05 and sig 0.018 <0.05. Then Ha is accepted and H0 is rejected. Variable X2 The development of residual operating income has a significant effect on the development of cooperatives, the value is known to be tcount 4.134 > ttable 2.05 and sig 0.000 <0.05. Then Ha is accepted and H0 is rejected. From the f test conducted, it was found that Member Participation and the Development of Remaining Operating Results have a simultaneous effect on Cooperative Development with fcount 18,859 > ftable 3,354 and significance (0.000 < 0.05). Then Ha is accepted and H0 is rejected. From the Determination Test the R Square value is 0.583. This means that the effect of the independent variable on the dependent variable is 58.3%, while the remaining 41.7% is influenced by other variables not intended in this study, such as Promotion, Coaching and Member Loyalty.